Organizational Culture and Motivation Affect Employee Job Satisfaction at LPD Badung Regency - Komang, Arik Krisna Dewi Ni; Ketut, Merta I; Made, Widani Ni (International Journal of Management and Business Intelligence, 2024)
This study focuses on LPD in Badung Regency. The objective is to test whether Organizational Culture and Motivation influence Employee Job Satisfaction by applying the Grand Theory of Stewardship (Davis et al., 1997). The research method used is Multiple Regression Quantitative with 93 samples, analyzed using SPSS Version 24. Research Results the Organizational Culture variable (X1) has a significant positive effect on job satisfaction at LPD in Badung Regency, The Motivation variable (X2) has a significant positive effect on job satisfaction at LPD in Badung Regency, Job Satisfaction (Y) has a significant positive simultaneous effect on organizational culture, motivation, and job satisfaction, which can therefore be simultaneous at the Village Credit Institutions in Badung Regency. Implications this research can provide answers regarding the influence of organizational culture and motivation variables on employee job satisfaction within the behavior of Village Credit Institutions in Badung Regency. The impact is substantial.